2013
DOI: 10.1590/s0101-41612013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliando o efeito contágio entre economias durante crises financeiras

Abstract: O objetivo deste trabalho, a partir das metodologias sugeridas por Forbes e Rigobon (2002) e Corsetti, Pericoli e Sbracia (2005), é verificar indícios de efeito contágio entre quinze economias em oito episódios de crises financeiras. Conclui-se que o modelo de Corsetti, Pericoli e Sbracia (2005), como esperado, apresentou-se mais eficiente em encontrar indícios de efeito contágio, uma vez que abrange variações nas componentes dos retornos não consideradas pelo modelo de Forbes e Rigobon (2002). Os resultados, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 5 publications
2
7
0
11
Order By: Relevance
“…As noticed, all countries had high peaks of volatility during the subprime crisis, as evidenced by Perobelli et al (2013). This crisis occurred from September 26, 2007, to March 17, 2009, which affected these markets afterward.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…As noticed, all countries had high peaks of volatility during the subprime crisis, as evidenced by Perobelli et al (2013). This crisis occurred from September 26, 2007, to March 17, 2009, which affected these markets afterward.…”
Section: Resultsmentioning
confidence: 82%
“…Following the model of Corsetti et al (2005), Perobelli, Vidal & Securato (2013) found that the Asian crisis of 1997 had the most contagion effect on the other markets. The other ones were the terrorist attacks of September 11, the Brazilian crisis of 1999, the internet bubble of 2000, and the subprime crisis; other events had only restricted shocks on the origin countries.…”
Section: Markets Correlations and Contagion Effectmentioning
confidence: 99%
“…The subprime crisis resulted in an acute change in all indices because the effects spilled over into other countries; Hemche et al (2014) showed that this led to an increase in dynamic correlations following the crisis period for most markets relative to the country from which the risk propagated. The volatility of the returns mirrored the effects of internal crises on the analyzed markets, such as what occurred in Brazil and Argentina in the early 2000s and the persistent effect of the subprime crisis in these economies (Perobelli et al , 2013).…”
Section: Resultsmentioning
confidence: 85%
“…The crises have presented different degrees of shocks according to their country of origin. Signs of contagion in a developed country were evident when a crisis happened, while signs of contagion were not evident in developing countries for all crises (Perobelli et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aparentemente, observa-se uma propagação da crise. Pode-se constatar tal fenômeno no passado recente, com as "crises" do México em 1994, da Rússia em 1998, no Brasil em 1999, e na Argentina em 2002 Esse contexto despertou uma série de estudos internacionais, com destaque para os de Chen e So (2002), Forbes e Rigobon (2002), Maroney et al (2004), Choudhry (2005), Choudhry et al (2010); e nacionais, como os de Marçal e Pereira (2008), Marçal et al (2011) e Perobelli et al (2013).…”
Section: Introductionunclassified